Growth, varietal development and cultivar diversity in seed production chain of cluster bean (Cyamopsis tetragonoloba) in India - CHAUHAN, J S; SINGH, K H; CHOUDHURY, P R; SINGH, R K; MISHRA, J P (The Indian Journal of Agricultural Sciences, 2023)
India with a contribution of about 90% to the global production ranks first in the world in cluster bean (Cyamopsis tetragonoloba [L.] Taub.) production. It is an important feed, fodder, food and industrial crop grown in arid and semiarid regions of West and North-West India specifically, Rajasthan, accounted for about 87.7% of the production and 91.5% of the acreage during 2020–21. India is also the major exporter of guar gum or derivatives in the international market and during 2022–23, earned valuable foreign exchange worth US 617.14 million by exporting 0.41 million tonnes (mt) of guar gum. During 2020–21 area, production and yield were reduced by 34.6%, 34.0% and 17.1%, respectively, over that of the 2010–11. The compound annual growth rate during the last five years of the decade was -12.4%, -17.5 and -5.7% for acreage, production and yield, respectively. Despite negative CAGR for area during the last twenty years, the production and yield of cluster bean increased with a CAGR of 4.5 and 5.1%. A total of 39 forage or grain type varieties of cluster bean were released and notified during 1976–2023. Varieties HG 2-20 (14.1–45.2%; 8/8) followed by RGC 1038/Guar Karan (1.4–16.7%; 8/8); HG 365 (0.3–10.0%, 8/8) and RGC 1033 (14.9–62.0%; 7/8) were the major contributors with highest frequency of occurrence in the top-most five varieties in the seed chain. Seed requirement for the next five years was assessed. Timely availability of adequate quantity of quality seed at affordable price requires holistic approach involving researchers and developmental personnel responsible for production of seed from both public and private sector.